Answer:
x^2 + 2x - 3 / x + 3 = x - 1
4abc / 16 = abc / 4
x2 - x - 2 / x - 1 = ( x + 1 ) ( x - 2 ) / ( x - 1 )
15mn / 35mn = 3 / 7
Explanation:
x^2 + 2x - 3
= x^2 - x + 3x - 3
= x ( x - 1 ) + 3 ( x - 1 )
= ( x + 3 ) ( x - 1 )
x^2 + 2x - 3 / x + 3
= ( x + 3 ) ( x - 1 ) / ( x + 3 )
= x - 1
4abc / 16
= 4 * abc / 4 * 4
= abc / 4
x^2 - x - 2
= x^2 + x - 2x - 2
= x ( x + 1 ) - 2 ( x + 1 )
= ( x + 1 ) ( x - 2 )
x^2 - x - 2 / x - 1
= ( x + 1 ) ( x - 2 ) / ( x - 1 )
15mn / 35mn
= 3 x 5 x mn / 5 x 7 x mn
= 3 / 7